PRAKTEK PENGELOLAAN SUMBER DAYA MANUSIA TERHADAP KINERJA PELAYANAN MELALUI KEPUASAN KERJA PADA MASKAPAI PENERBANGAN KOMERSIAL DI INDONESIA - Deddy Wibowo Adhinugroho (Jurnal Manajemen dan Pemasaran Jasa, 2015)
This research is to present the effect of Human Resources Practices on Performance in Service Quality Through Employee Satisfaction In Commercial Scheduled Passenger Airlines in Indonesia” by referring to previous research conducted by Michel Rod and Nicholas J. Ashill (2010) as the main reference, and its equipped with research conducted by Jochen Wirtz, Loizos Heracleus, and Nitin Pangarkar (2008). The research background is to analyze the job performance in quality service as an important element to win the competition in the aviation services industry. The objective of this research was to examine the influence of Human Resources Practices for Performance in Quality Service, through job satisfaction. The research design is using primary data obtained by distributing questionnaires to 110 of front line employees on airlines companies in Indonesia. Data analysis method used is Structural Equation Model (SEM). Results of this study concluded that there is a positive effect of training, empowerment, Customer Service Orientation, and rewards, as part of the Human Resources Practices for Performance in Service Quality, through job satisfaction.